The Effectiveness of Implementing the Teaching-at-the-Right-Level (TaRL) with Number-Board Media Improves Elementary Students’ Integer Learning Outcomes - Wawan Syahiril; Vania Angelia Putri; Wita Anggraini; Risna Sasmita (MASI Mandiri Edukasi, 2025)
Understanding the concept of Integers remains a significant challenge for many elementary school students, particularly in grasping the concept of place value. This study aims to evaluate the effectiveness of the Teaching at the Right Level (TaRL) approach, assisted by number board media, in improving the learning outcomes of fifth-grade students in Integer material. A quantitative method with a one-group pretest-posttest pre-experimental design was employed, involving 24 students from SDN Bantarkemang 6 selected through purposive sampling. Data were collected using a 10-item multiple-choice test administered before and after the intervention. The results show an increase in the average score from 68.33 (pretest) to 87.08 (posttest). The Wilcoxon Signed-Rank Test revealed a significance value of 0.001 (p < 0.05), indicating a statistically significant improvement. The N-Gain score of 0.6604 was classified as moderate, supporting the conclusion that the TaRL approach, combined with number board media, is effective in enhancing students’ learning outcomes in Integers concepts.